Pendampingan Pencegahan Penyebaran Nyamuk Demam Bedarah dengan "FOOGING" Bersama Anak Karang Taruna Desa Wudi - Isna Finurika; Ahmad Eko Cahyo Subaktiar; Abdul Munif; Ahmad Naufal Hanif Pasaribu; Achsani Taqwim (Santri: Journal of Student Engagement, 2023)
Dengue Hemorrhagic Fever (DHF) is one of the many dangerous diseases in the world. This disease, which is caused by the Aedes aegypti and Aedes albopictus mosquitoes, has claimed many human lives since it first appeared. Indonesia, which has a tropical climate and has a green area, is a very big supporting factor for the development of this very dangerous mosquito, because the development of the Aedes aegypti and Aedes albopictus mosquitoes usually develops in places that tend to be humid and watery, so many cases have occurred. caused by this relatively small but very deadly animal. and Wudi Village, Sambeng District, Lamongan Regency, this is one of the strategic places for the development of this mosquito, because the settlement is very close to fields and forests so it is very possible for the spread of this Aedis mosquito to breed very quickly. To analyze the problem, we used the observation method by visiting and asking local residents. From the results we get, residents are also disturbed by the number of mosquitoes that appear in their settlements, therefore we provide a solution to the problem in the form of fooging activities, namely spraying mosquito repellent to overcome this problem so that the development of ordinary mosquitoes or dangerous mosquitoes such as Aedes aegypti and Aedes albopictus can its existence is minimized so that the villagers are not disturbed anymore because of that we are working with the village head and youth youth groups to carry out this fooging activity so that it runs smoothly and can be welcomed positively by all residents.